PENYULUHAN PREVENTIF PERUBAHAN PERILAKU HIDUP SEHAT: CEGAH DIRI DARI BAHAYA NARKOBA DI SALAH SATU SMAN CIMAHI – JAWA BARAT - Widyastuti, Linda; Ika Kurnia Sukmawati,; Denni Fransiska Helena Marpaung,; Karimah, Karimah; Melysa, Melysa (JURNAL PENGABDIAN MANDIRI, 2024)
Counseling as an activity to increase knowledge and awareness of the impact of drugs on health, in addition to attitudes and actions of healthy living behavior at one of SMAN Cimahi. Using material exposure devices through booklets and posters as well as assessment instruments. The purpose of this activity is to determine the effectiveness and implementation of counseling. The sample in this study were class XII students, totaling 84 people. Data were collected using test techniques in the form of pretest-posttest via the g-form link, non-tests in the form of questionnaires and observations, as well as documentation. Data analysis technique using frequency distribution analysis. The results showed that: 1) The effectiveness of counseling was seen from the results of the pretest-posttest of knowledge and attitudes which experienced a significant increase and 2) The implementation of counseling was seen from the interest of the extension participants and the observation of extension activities with a very good acceptance category. This indicates that the application of extension tools has an effect on increasing knowledge and attitudes related to extension materials.